(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تسعى هذه الدراسة إلى تصميم نظام محاكاة صالح للتطبيق على المصارف التجارية, هذا النظام سيكون بمثابة مجتمع دراسة افتراضي يمثل مجتمع الدراسة الحقيقي. تهدف الدراسة من استخدام أسلوب المحاكاة إلى توفير أداة بحثية أكثر فعالية في مراقبة بيانات وكائنات النظام الحقيقي مثل: تدفق العملاء من حيث الحجم والتوقيت والنوع والمسارات, توزع مقدمي الخدمة, أزمنة إنجاز العمليات المصرفية. يقوم نموذج المحاكاة المصمم بإعادة توليد العملاء باستخدام الطلب المجدول, وتصميم الكائنات من عمليات ومحطات, وتحديد مسارات تلقي الخدمات آلياً. يستدل من خلال هذا النظام على وجود فجوات بين العرض والطلب على الخدمات المصرفية, من خلال مراقبة تشكل صفوف الانتظار. تم الاعتماد على بيانات المصرف التجاري السوري فرع //4 دمشق في بناء نموذج المحاكاة المصرفي كمشروع إرشادي. توصلت الدراسة إلى نتيجة هامة مفادها: أن عرض الخدمات المصرفية للمصرف المذكور لم تكن كافية لمقابلة الطلب عليها, وأن توزيع العبء على الموظفين لم يكن عادلاً. This study seeks to design a simulation system applicable to commercial banks. This system will serve as a virtual study population, representing the real study population. The aim of the study is to use a simulation model to provide a more effective research tool for monitoring real system data and objects such as: flow of customers in size, timing, type and path, distribution of service providers, time of completion of banking operations. The designed simulation model recreates customers using tabular demand, as well as designs objects of processes and stations, and routing of services automatically. This system shows if there is a gap between the supply and demand of banking services by monitoring the formation of Queue. The commercial bank of Syria- branch 4, in Damascus has been relying on building the banking simulation model as a pilot project. The study conclusion showed that the bank’s offer of banking services was not sufficient to meet the demand, and that the distribution of the burden on staff was not fair.